Pengujian Terhadap Aplikasi Parking Management Menggunakan Metode Black-Box Berbasis Equivalence Partitions - Fauzi, Fahmi Ahmad; Putra, Gunawan Eka; Supriyanto, Supriyanto; Saputra, Nurul Asia; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Testing is a process in implementing a program for the purpose of finding / looking for an error. A test case is said to be good is if the test to be performed has the possibility of finding an error that cannot be revealed. While testing is said to be successful if the test to be carried out successfully found an error that originally could not be found. This research was tested by applying the Black Boxt Testing method. There are several ways in the Black Box Testing method, namely Boundary Value Analysis, Comparison Testing, Sample Testing, Robustness Testing, Equivalence Partitioning and others. In this study using testing by Equivalence Partitioning. Equivalence Partitioning Analysis is a case / problem that will be tested by finding several errors and reducing / minimizing the number of cases that must be made. This test is performed on the Parking Management Application function to facilitate managing parking. The test results indicate the application is in accordance with needs.